Reliability of Tethered Swimming Evaluation in Age Group Swimmers - Amaro, Nuno (2020)
The aim of the present study was to examine the reliability of tethered swimming in the evaluation of age group swimmers. The sample was composed of 8 male national level swimmers with at least 4 years of experience in competitive swimming. Each swimmer performed two 30 second maximal intensity tethered swimming tests, on separate days. Individual force-time curves were registered to assess maximum force, mean force and the mean impulse of force. Both consistency and reliability were very strong, with Cronbach's Alpha values ranging from 0.970 to 0.995. All the applied metrics presented a very high agreement between tests, with the mean impulse of force presenting the highest. These results indicate that tethered swimming can be used to evaluate age group swimmers. Furthermore, better comprehension of the swimmers ability to effectively exert force in the water can be obtained using the impulse of force.